Suicide : Leading Cause of Death among Women in Nepal - Karki, C (Kathmandu University Medical Journal, 2012)
No abstract available. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6294 Kathmandu Univ Med J 2011;9(3):157-8